LITERASI MEDIA DIGITAL MAHASISWA SURAKARTA DALAM MENSIKAPI HOAX DI MEDIA SOSIAL - Nurnawati Hindra Hastuti, Buddy Riyanto & (Transformasi, 2017)
Descriptive qualitative research titled " Digital Media Literacy of Undergraduate Student ofSurakarta In Dealing with Hoaxes in Social Media " is motivated by the rise of hoaxes in socialmedia. And even the viral in the student WhatsApp group incidentally includes the intellectualsand future leaders of Indonesia. Data collection method in this research is done by interview,observation and document searching. The data validity was obtained by triangulation, the datawas analyzed irreverently with reference to New Media Literacy theory by Jenkin et al. (2009).The results showed that the Surakarta undergraduate students have a fairly good level of DigitalMedia Literacy. They can also identify false news or hoax, but in their daily behavior they areless critical when receiving or accessing information so as to allow exposure to hoax eveninadvertently participating in Whatsapp social media.Keywords: digital media literacy, hoaxes, undergraduate students